2018
DOI: 10.18632/oncoscience.413
|View full text |Cite
|
Sign up to set email alerts
|

Non-selective beta blockers inhibit angiosarcoma cell viability and increase progression free- and overall-survival in patients diagnosed with metastatic angiosarcoma

Abstract: Patients with metastatic angiosarcoma undergoing chemotherapy, radiation, and/or surgery experience a median progression free survival of less than 6 months and a median overall survival of less than 12 months. Given the aggressive nature of this cancer, angiosarcoma clinical responses to chemotherapy or targeted therapeutics are generally very poor. Inhibition of beta adrenergic receptor (β-AR) signaling has recently been shown to decrease angiosarcoma tumor cell viability, abrogate tumor growth in mouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 82 publications
1
42
0
2
Order By: Relevance
“…The targets of propranolol, the beta adrenergic receptor proteins (β-AR1, β-AR2, β-AR3), are expressed in angiosarcoma [ 25 , 27 ]. Preclinical studies using in vitro and in vivo angiosarcoma models indicate that propranolol as a single agent is capable of reducing tumor cell proliferation, selectively inducing tumor cell apoptosis while sparing non-diseased cell types, and inhibiting the growth of angiosarcoma xenografts in animal tumor models [ 23 , 25 , 26 ]. Translation of these findings into human patients revealed that propranolol alone is capable of reducing the angiosarcoma proliferative index after only 1 week of treatment [ 20 ], however the long term efficacy of propranolol as a single agent therapy was not individually evaluated in the aforementioned study, as the tumor was subsequently treated with radiation and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The targets of propranolol, the beta adrenergic receptor proteins (β-AR1, β-AR2, β-AR3), are expressed in angiosarcoma [ 25 , 27 ]. Preclinical studies using in vitro and in vivo angiosarcoma models indicate that propranolol as a single agent is capable of reducing tumor cell proliferation, selectively inducing tumor cell apoptosis while sparing non-diseased cell types, and inhibiting the growth of angiosarcoma xenografts in animal tumor models [ 23 , 25 , 26 ]. Translation of these findings into human patients revealed that propranolol alone is capable of reducing the angiosarcoma proliferative index after only 1 week of treatment [ 20 ], however the long term efficacy of propranolol as a single agent therapy was not individually evaluated in the aforementioned study, as the tumor was subsequently treated with radiation and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Translation of these findings into human patients revealed that propranolol alone is capable of reducing the angiosarcoma proliferative index after only 1 week of treatment [ 20 ], however the long term efficacy of propranolol as a single agent therapy was not individually evaluated in the aforementioned study, as the tumor was subsequently treated with radiation and chemotherapy. Non-randomized prospective and retrospective studies have combined propranolol with conventional anti-sarcoma therapies, leading to substantially increased progression free- and overall-survival of angiosarcoma patients [ 23 , 26 ], however randomized clinical studies are necessary to comprehensively evaluate the efficacy and optimal dosing of propranolol against angiosarcoma. Several targeted therapeutics such as Pazopanib, TRC105, and others are currently being tested clinically against this tumor type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, PPN demonstrated to reverse protumoral effects mediated by stress hormones in chronic or surgical stress models, reducing angiogenesis and metastasis, and increasing immune function [10,15]. Taking all these data into account, assessment of PPN anticancer properties has recently reached clinical stages for angiosarcoma, ovarian cancer and melanoma, mainly as a surgical adjuvant or in combination with chemotherapy or biologic targeted therapy [16][17][18]. Despite sympathetic nervous system (SNS) activation and signaling pathways triggered by catecholamines such as epinephrine and norepinephrine are deeply involved in cancer initiation and progression [19,20], little is known about the speci c role of catecholamines or β-AR signaling in OSA.…”
Section: Introductionmentioning
confidence: 99%
“…11 12 The pharmacological effects of propranolol in infantile haemangioma are presumed to cause vasoconstriction, a decreased expression of vascular endothelial growth factor (VEGF) and basic fibroblast growth factor, inhibition of migration and proliferation of tumour cells and induction of apoptosis of endothelial cells. [12][13][14][15][16] Angiosarcoma have several similarities with infantile haemangioma, including its high β-adrenergic receptor expression and the suggested important role of VEGF in malignant growth. 14 17 18 Several small case reports and case series have confirmed the idea that propranolol could be repurposed to treat angiosarcoma.…”
mentioning
confidence: 99%